(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article highlights the issues of developing children’s abilities in the preschool education system through the application of differential and integrative approaches. The study analyzes the pedagogical significance of organizing the educational process by taking into account the individual, personal, and psychophysiological characteristics of preschool children. The differential approach enables the creation of educational conditions that correspond to children’s interests, inclinations, and abilities. Meanwhile, the integrative approach provides opportunities to develop modern thinking, creativity, and cognitive activity by harmonizing various types of activities.